APPLICATION OF METHOD FISH (FLUORESCENCE $IN~SITU$ HYBRIDIZATION) IN PRENATAL AND POSTNATAL DIAGNOSTICS OF CHROMOSOMAL ANOMALIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
For the first time the molecular-cytogenetic method of fluorescence in situ hybridization (FISH) was widely used in Armenia in prenatal and postnatal diagnostics of 30 patients with different forms of chromosomal pathology. Application of FISH method in cytogenetic practice of Armenia increased the efficiency of diagnostics of chromosomal anomalies.
Keywords: molecular-cytogenetic method; fluorescence $in~situ$ hybridization; chromosomal pathology; chromosomal anomalies